Pembentukan Karakter Anak Melalui Kesenian Gondang Anak Di Sanggar Seni Damar Wulan Desa Parumasan Kecamatan Sodonghilir - Kevin Jayakusumah; Asep Wasta; Asti Tri Lestari (CV. ITTC INDONESIA, 2026)
This study aims to describe the learning process of Gondang Anak art at the Damar Wulan Art Studio in Parumasan Village, Sodonghilir District, and analyze how these activities play a role in shaping children's character. Gondang art, as an agrarian cultural heritage of the Sundanese people, has strong social and spiritual values, such as mutual cooperation, discipline, responsibility, and togetherness. In a modern context, the involvement of children in Gondang activities at the Damar Wulan Studio is a strategic effort to preserve local culture while instilling positive character values ​​from an early age. The research method used is a qualitative case study approach. Data were collected through observation, interviews, and documentation of the studio leaders, trainers, and children participating in the activities. Data analysis uses the Miles and Huberman model, including data reduction, data presentation, and drawing conclusions. The research results show that the Gondang learning process is carried out in stages through imitation and repetition methods, where the trainer provides direct examples that the children then follow. This activity not only improves musical skills but also fosters character traits of discipline, cooperation, self-confidence, responsibility, and social awareness. Changes in children's behavior are evident in increased time discipline, ability to work in groups, and courage to perform in public. Thus, Gondang Anak art has proven effective as a medium for character education based on local culture. This activity not only preserves traditional Sundanese art but also strengthens the cultural and moral identity of the younger generation amidst the current of globalization.